Using the Biological Condition Gradient Model as a Bioassessment Framework to Support Rehabilitation and Restoration of the Upper Tana River Watershed in Kenya - Ndiritu, George G.; Terer, Taita; Njoroge, Peter; Muiruri, Veronica M.; Njagi, Edward L.; Kosgei, Gilbert; Njoroge, Laban; Kamau, Peris W.; Malonza, Patrick K.; Muchane, Mary; Gathua, Joseph; Odeny, Dickens; et al. (Frontiers in Environmental Science, 2021)
The Biological Condition Gradient (BCG), a scientific framework that describes the change in ecosystem characteristics in response to human-induced levels of stressors was modified and used to characterise watershed habitats in Upper Tana River watershed, Kenya. The inbuilt utilities of BCG, including its simplicity, versatility and its robust nature allowed its use by seven taxonomic groups of macroinvertebrates, diatoms, fish, herpetofauna (amphibians and reptiles), plants, macro-fungi and birds to assess and monitor landscape conditions in both terrestrial and aquatic habitats. The biological data were described using taxa abundance distribution measures followed by multivariate analyses to determine their relationship with water or soil quality and thereafter assessment of taxa tolerant levels and functional characteristics in response to environmental stress and disturbances. Preliminary findings found taxonomic groups complement each other, with each taxonomic group reliably assessing ecological conditions to a certain degree that supported assigning all the 36 sampled sites into BCG Tiers. BCG models developed for each taxonomic groups assisted in the identification and selection of taxa indicating varying levels of landscape conditions. These taxa, referred to as flagship or indicator taxa, assist in simplifying the BCG model, hence possible for use by parataxonomists or ordinary citizens to assess and monitor the ecological health of habitats under consideration. Further, the capability of BCG models to assess landscape conditions shows how they can be used to identify high-quality habitats for conservation, to direct investment for restoration, and track progress.